Influence of platform governance on users’ value co-creation: empirical evidence from crowdsourcing logistics platform in China - Ke, Tongping; Xiao, Liang (Industrial management + data systems, 2025)
PurposeUsers’ active participation in platform value co-creation is the key to the development of crowdsourcing logistics platforms, especially the active participation of the crowdsourcee who provide logistics services. However, driven by self-interest, coupled with loose links among subjects on the platform ecological chain, it is difficult for users to effectively form value co-creation intentions. This study aims to explore how platform governance affects crowdsourcees’ intention to participate in value co-creation on the platform through individual cognition.Design/methodology/approachBased on social cognitive theory (SCT), this study built a research model and took the crowdsourcee on China’s well-known crowdsourcing logistics platforms as the investigation object, using the collected 302 valid survey data to test the model.FindingsThe results showed that platform governance mechanisms have a significant influence on crowdsourcees’ intention to participate in value co-creation on the platform, either directly or through crowdsourcee cognition, and the impact is different. The crowdsourcee cognition plays a mediating role between platform governance mechanisms and crowdsourcees’ intention to participate in value co-creation on the platform, and the mediating effect of value acquisition perception (VAP) is significantly higher than self-efficacy (SE).Originality/valueThe results provided references for crowdsourcing logistics platforms to develop a targeted governance mechanism to promote the platform to achieve value co-creation.